Report of the Expert Committee on Public Health System - Planning Commission (Planning Commission, 1996)
India is a large country with around 900 million population in 25 states and 7 Union Territories. Historically India had a rich public heath system as evidenced from the relics of Indus Valley civilisation demonstrating a holistic approach towards care of human and disease. The public health system declined through the successive invasions through the centuries, intrusion of modern culture and growing contamination of soil, air and water from population growth. With the establishment of British rule and the initiation of practice of Western medicines in India strong traditional holistic public health practice in India went into disuse bringing disease-doctor-drug orientation.
Government of India Ministry of Health & Family Welfare
Government of India Ministry of Health & Family Welfare